Acetylcholine polarizes dendritic cells toward a Th2‐promoting profile. Issue 2 (30th June 2016) - Gori, S.; Vermeulen, M.; Remes‐Lenicov, F.; Jancic, C.; Scordo, W.; Ceballos, A.; Towstyka, N.; Bestach, Y.; Belli, C.; Sabbione, F.; Geffner, J.; Salamone, G.
Abstract: Background: A growing body of research shows a reciprocal regulation between the neural and immune systems. Acetylcholine (ACh) is the most important parasympathetic neurotransmitter, and increasing evidence indicates that it is able to modulate the immune response. Interestingly, in recent years, it has become clear that immune cells express a non‐neuronal cholinergic system, which is stimulated in the course of inflammatory processes. We have previously shown that dendritic cells (DC) express muscarinic receptors, as well as the enzymes responsible for the synthesis and degradation of ACh. Here, we analyzed whether ACh could also modulate the functional profile of DC. Methods: Dendritic cells were obtained from monocytes cultured for 5 days with GM‐CSF+IL‐4 or isolated from peripheral blood (CD1c+ DC). The phenotype of DC was evaluated by flow cytometry, the production of cytokines was analyzed by ELISA or intracellular staining and flow cytometry, and the expression of muscarinic and nicotinic receptors was evaluated by flow cytometry or qRT‐PCR. Results: Treatment of DC with ACh stimulated the expression of the Th2‐promoter OX40L, the production of the Th2‐chemokines MDC (macrophage‐derived chemokine/CCL22) and TARC (thymus and activation‐regulated chemokine/CCL17), and the synthesis of IL‐4, IL‐5, and IL‐13 by T cells, in the course of the mixed lymphocyte reaction (MLR). Moreover, we found that the stimulation of OX40L, HLA‐DR, and CD83 expressions in DC induced by the Th2‐promoting cytokine TSLP, as well as the production of IL‐13, IL‐4, and IL‐5 by T cells in the course of the MLR, was further enhanced when DC were treated with TSLP plus ACh, instead of TSLP or ACh alone. Conclusions: Our observations suggest that ACh polarizes DC toward a Th2‐promoting profile.